Effects of artificial canopy shading on vegetative growth and ripening processes of cv. Nero d’Avola (Vitis vinifera L.) - Miccichè, Daniele; de Rosas, Maria Inès; Ferro, Massimo Vincenzo; Di Lorenzo, Rosario; Puccio, Stefano; Pisciotta, Antonino (Frontiers in Plant Science, 2023)
The biology of the grapevine (Vitis vinifera L.) is clearly influenced by the climatic conditions of the growing environment, where temperature and light play a major role in modifying plant physiology. In the scenario of climatic changes, radiative excess, correlated to the increase in temperature, can concretely subject the photosynthetic apparatus to a condition of light saturation and cause a drastic reduction in photochemical efficiency, giving rise to chronic photoinhibition phenomena. The objective of this study was to determine how artificial canopy shading affects the vines vegetative growth and the ripening processes of Vitis vinifera cv. Nero d'Avola during the 2019-2020 vegetative seasons. Three treatments were established: shading treatment with a green net (shade factor 27%), shading treatment with a white net (shade factor 32%), and untreated vines, thus naturally exposed to light radiation. Artificial shading, applied at full fruit set, interfered with the microclimate of the vines, causing partial effects on the grape ripening processes. At harvest, no significant differences were found between the treatments in terms of sugars, while shading treatments increased must acidity and decrease pH. Results obtained on vegetative parameters, suggest that the shading treatment delays leaf fall, with potentially positive effects on the starch accumulation on perennial reserve organs to be exploited at the following season's sprouting. Shading significantly reduced berry size, with obvious consequences on bunch weight and yield per vine. In 2020, shaded plants showed a delay in all the phenological phases. The total anthocyanins content was not changed by the shading treatment. The results obtained confirm the importance of net coverage on the microclimate of the vines, vegetative-productive activity, and grapes quality. From this point of view, the net covering technique can be a tool for controlling grapes ripening dynamics in the context of climate change.